Pengaruh Pola Asuh Orang Tua Terhadap Perkembangan Sosial Emosional dan Motivasi Belajar Siswa di Sekolah Dasar - Lina Riyani; Ima Mulyawati (Jurnal Elementaria Edukasia, 2023)
Parents are the first environment to influence the process of children's growth and development, especially social-emotional development. Therefore, parenting style is closely related to child development because the parents spend the most time with children. The aim of this research is to ascertain how childcare practices are related to learning motivation and social-emotional development. This research was conducted at SDN Ciganjur 02 Pagi using associative quantitative methods and data collection procedures in the form of observation, surveys, and documentation. 64 grade II students at SDN Ciganjur 02 Pagi became the research sample. Data processing in this study using the t-test. The results of the study show that there is a relationship between the principles of parenting with social social-emotional growth. Thus, parents significantly influence the socio-emotional development of elementary school students to encourage learning motivation.